Analisis Pengembangan Modul IPS Perbedaan Nilai Mata Uang Berbasis PjBL untuk Meningkatkan Keterampilan Berpikir Kritis Siswa Kelas IV SD - Ane, Syirilia Regina; Rusmawan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Critical thinking skills are essential competencies that need to be developed from the elementary school level, particularly in Social Studies learning, which requires analytical and decision-making abilities. However, current Social Studies learning practices in elementary schools have not optimally facilitated the development of students’ critical thinking skills. This study aims to analyze the condition of fourth-grade students’ critical thinking skills, identify teachers’ efforts to enhance these skills, and examine the urgency of developing a Project Based Learning (PjBL)-based Social Studies module as an alternative learning resource. This research employed a descriptive qualitative approach and was conducted in several elementary schools in Yogyakarta. The research subjects consisted of three fourth-grade teachers who were interviewed in depth and eighteen fourth-grade students who were observed over a one-month period. Data were collected through interviews and observations and analyzed using the interactive analysis model of Miles and Huberman, which includes data reduction, data display, and conclusion drawing. The findings indicate that students’ critical thinking skills, particularly in providing simple explanations and drawing conclusions from ideas or arguments, have not yet developed optimally. Students tend to lack confidence, experience difficulty in expressing ideas coherently, and require continuous guidance from teachers. Although teachers have implemented various instructional strategies, such as presentations and practical activities, the absence of structured and contextual learning modules remains a significant limitation. Therefore, the development of a Project Based Learning-based Social Studies module is considered essential to support meaningful learning and strengthen elementary students’ critical thinking skills.